A Trust model based on a time decay factor for use in social networks. (July 2020) - Jiang, Jiulei; Wang, Hanxu; Li, Weimin
Abstract: The rapid development of social networks has increased the online interaction of users in many ways and trust plays an important role. Due to the structure of current social network platforms, most users are unfamiliar with each other. Therefore, trust modeling is a meaningful topic for users who have not been exposed to social networks to determine whether a strange user is trustworthy. In this paper, for the trust value evaluation problem, context-based multiple factors are used in the selection of trust features to overcome the coarseness of the traditional trust model. A time decay factor is included to characterize the dynamics of trust. The experimental results show that the proposed model is capable of accurately calculating the dynamic trust between users.